ANALYSIS OF TSS VALUE CHANGES IN 2020-2023 USING SENTINEL-2A IMAGES IN KUTA WATER AREA OF SOUTH LOMBOK - NI MADE NIA BUNGA SURYA DEWI (GANEC SWARA, 2023)
It is very important to monitor water quality to find out the extent to which human activities affect the quality of water used to support human life. The existence of the Mandalika Circuit, which is now the Indonesian MotoGP circuit, has boosted tourism in the Kuta area of South Lombok. The quality of the waters in the Kuta area of South Lombok will undoubtedly decline due to this tourism activity. Using remote sensing methods to measure water quality, this research examines the level of pollution and changes in water quality in Kuta, South Lombok, before the 2020 MotoGP event and after the 2023 MotoGP event. Using the TSS algorithm from Sentinel-2A imagery in 2020 and 2023, this study determines changes in water quality. There was a significant increase in the content of TSS in the waters of Kuta, South Lombok from 2020 and 2023. Pollution meeting quality standards in 2020 was 0.027mg/L l which is below the detection limit (Detection limit = 0.5 mg/L), but increased in 2023 by 21.79 mg/L. Furthermore, the level of pollution is classified using the pollution index issued by the State Minister for the Environment Number 1 year 2010 that the waters of Kuta, South Lombok are still clean and awake